Investigation on syngas production via biomass conversion through the integration of pyrolysis and air-steam gasification processes - Alipour Moghadam, R. (Elsevier Ltd, 2014)
Fuel production from agro-waste has become an interesting alternative for energy generation due to energy policies and greater understanding of the importance of green energy. This research was carried out in a lab-scale gasifier and coconut shell was used as feedstock in the integrated process. In order to acquire the optimum condition of syngas production, the effect of the reaction temperature, equivalence ratio (ER) and steam/biomass (S/B) ratio was investigated. Under the optimized condition, H2 and syngas yield achieved to 83.3 g/kg feedstock and 485.9 g/kg feedstock respectively, while LHV of produced gases achieved to 12.54 MJ/N m3. Â© 2014 Elsevier Ltd. All rights reserved.